A cyber physical system (CPS) approach for safe human-robot collaboration in a shared workplace. (April 2019) - Nikolakis, Nikolaos; Maratos, Vasilis; Makris, Sotiris
Highlights: A cyber physical system for human collision risk detection is examined. A first implementation of the CPS was implemented and tested. A closed-loop control for applying safety policies to the operators was realised. A human robot collaborative scenario was used for testing the CPS. Short response times of the CPS demonstrates potential for real world application. Abstract: Modern manufacturing systems require increased levels of automation for fast and low-cost production, but also high levels of flexibility and adaptability to dynamic production requirements. Human-robot interaction allows for closer collaboration in assembly tasks that require increased productivity by combining the performance of robotic systems with the flexibility and dexterity of human workers. However, the main challenge is establishing human safety while performing near to robots. Towards enabling safe human-robot collaboration several physical and software systems should be combined. In this paper, a cyber-physical system for enabling and controlling safe human-robot collaborative assembly operations is discussed. The approach considers a shared fenceless working space where humans, industrial robots, or other moving objects, such as auto-guided vehicles, may operate. The working space is monitored by optical sensors. In this context, human safety is the major challenge. The paper focuses on a Cyber-Physical System for enabling human-robot collaboration based on real-time evaluation of safety distance and a closed-loop control for triggering collision preventive actions. An initial implementation is evaluated in a specific use case in a laboratory machine shop with an industrial robot, and its results are compared regarding the use of one or more sensors. The comparison is performed in terms of system response time to detect human presence within a predefined safety zone.